Ablation of the Chaperone Protein ERdj5 Results in a Sjögren's Syndrome-Like Phenotype in Mice, Consistent With an Upregulated Unfolded Protein Response in Human Patients - Apostolou, Eirini; Moustardas, Petros; Iwawaki, Takao; Tzioufas, Athanasios G.; Spyrou, Giannis (Frontiers in Immunology, 2019)
Objective Sjögren’s syndrome (SS) is a chronic autoimmune disorder that affects mainly the exocrine glands. Endoplasmic reticulum (ER) stress proteins have been suggested to participate in autoimmune and inflammatory responses, either acting as autoantigens, or by modulating factors of inflammation. The chaperone protein ERdj5 is an ER resident disulfide reductase, required for the translocation of misfolded proteins during ER associated protein degradation. In this study we investigated the role of ERdj5 in the salivary glands (SGs), in association with inflammation and autoimmunity. Methods In situ expression of ERdj5 and XBP1 activation was studied immunohistochemically in minor SG tissues from primary SS patients and non SS sicca complaining controls. We used the mouse model of ERdj5 ablation and characterized its features: Histopathological, serological (antinuclear antibodies and cytokine levels) and functional (saliva flow rate). Results ERdj5 was highly expressed in the minor SGs of SS patients, with stain intensity correlated to inflammatory lesion severity and anti SSA/Ro positivity. Moreover, SS patients demonstrated higher XBP1 activation within the SGs. Remarkably, ablation of ERdj5 in mice conveyed many of the cardinal features of SS, like spontaneous inflammation in SGs with infiltrating T and B lymphocytes, distinct cytokine signature, excessive cell death, reduced saliva flow, and production of anti-SSA/Ro and anti-SSB/La autoantibodies. Notably, these features were more pronounced in female mice. Conclusions Our findings suggest a critical connection between the function of the ER chaperone protein ERdj5 and autoimmune inflammatory responses in the SGs and provide evidence for a new, potent animal model of SS.